Exploring the characteristics of potential and current users of mobility scooters, among older people in Israel. (April 2017) - Gitelman, Victoria; Pesahov, Fany; Carmel, Roby; Chen, Sarit
Highlights: Scooters can serve as alternative mobility means for older people. People of older ages, with health problems and active lifestyle incline to use scooters. Scooter riders on sidewalks did not create conflicts with pedestrians. Scooter riders on roadways created dangerous situations. To stimulate scooter travels on sidewalks, urban infrastructure adjustments are required. Abstract: Recognizing the decline in the ability of older people to serve as vehicle drivers and their physical limitations for long walks, mobility scooters are considered as an alternative mobility means for older people. An increasing popularity of scooters is recently being observed in Israel, raising safety concerns. This study explored the characteristics of potential users of mobility scooters among older people in Israel and the behaviours of their current users, by means of an opinion survey and field observations in urban areas. The opinion survey applied structured interviews, with 110 persons aged 65+. The survey's results showed that most people agreed that scooters may improve their mobility and quality of life. However, they expressed a relatively low willingness to use scooters, mostly, due to the preference for private cars but also the lack of appropriate infrastructure for safe scooter travel in the city. An increasing potential for scooters' use was associated with ages 70–84, people who are aware of their health problems and less involved in physical activities but still maintain an active lifestyle, living independently and appreciating scooter benefits. The observations included 55 video-records with older scooter riders. They showed that regardless the types of urban road or junction, the majority of scooter riders behaved like a vehicle, i.e. travelled on the roadway. Scooters' moving on a sidewalk did not create conflicts with pedestrians, while scooters travelling on the roads sometimes disturbed vehicle flows and created dangerous situations. To ensure safety of the scooter users, their travels on the sidewalks should be stimulated and, thus, appropriate adjustments of urban infrastructure are required.